Diet was less significant than physical activity in the prognosis of people with sarcopenia and metabolic dysfunction-associated fatty liver diseases: Analysis of the National Health and Nutrition Examination Survey III - Yi, Yun; Wang, Chun; Ding, Yang; He, JiangHua; Lv, YuQing; Chang, Ying (Frontiers in Endocrinology, 2023)
Background: Sarcopenia is prevalent in metabolic dysfunction-associated fatty liver diseases (MAFLD), and the primary treatment for both diseases is lifestyle modification. We studied how dietary components and physical activity affect individuals with sarcopenia and MAFLD. Materials and methods: We conducted a study utilizing National Health and Nutrition Examination Survey (NHANES) III (1988–1994) data with Linked Mortality file (through 2019). The diagnosis of fatty liver disease (FLD) was based on ultrasound images revealing moderate and severe steatosis. Using bioelectrical measures, sarcopenia was assessed. Using self-report data, dietary intake and physical activity levels were evaluated. Results: Among 12,259 participants, 2,473 presented with MAFLD, 290 of whom had sarcopenia. Higher levels of physical activity (odds ratio [OR] = 0.51 [0.36–0.95]) and calorie (OR = 0.58 [0.41–0.83]) intake reduced the likelihood of sarcopenia in MAFLD patients. During a median follow-up period of 15.3 years, 1,164 MAFLD and 181 sarcopenic MAFLD patients perished. Increased activity levels improved the prognosis of sarcopenic patients (Insufficiently active, HR=0.75 [0.58-0.97]; Active, HR=0.64 [0.48–0.86]), which was particularly pronounced in older patients. Conclusion: In the general population, hyperglycemia was highly related to MAFLD prognosis. Physical inactivity and a protein-restricted diet corresponded to sarcopenia, with physical inactivity being connected to poor outcomes. Adding protein supplements would be beneficial for sarcopenic older people who are unable to exercise due to frailty, while the survival benefits were negligible.